The Role of the Interviewer in Producing Mode Effects: Results From a Mixed Modes Experiment Comparing Face-to-Face, Telephone and Web Administration - Steven Hope; Pamela Campanelli; Gerry Nicolaas; Peter Lynn; Annette Jäckle (Survey Research Methods, 2022)
The presence of an interviewer (face-to-face or via telephone) is hypothesized to motivate respondents to generate an accurate answer and reduce task difficulty, but also to reduce the privacy of the reporting situation. To study this, we used respondents from an existing face-to-face probability sample of the general population who were randomly assigned to face-to-face, telephone and web modes of data collection. The prevalence of indicators of satisficing (e.g., non-differentiation, acquiescence, middle category choices and primacy and recency effects) and socially desirable responding were studied across modes. Results show differences between interviewer modes and web in levels of satisficing (non-differentiation, acquiescence and middle category choices) and in socially desirable responding. There were also unexpected findings of (1) different ways of satisficing by mode and (2) of a telephone mode primacy/positivity effects.